Similar or Totally Different: the Adjustment of the Twist Conformation Through Minor Structural Modification, and Dramatically Improved Performance for Dye‐Sensitized Solar Cell. Issue 18 (14th July 2015) - Chai, Zhaofei; Wu, Mei; Fang, Manman; Wan, Sushu; Xu, Ting; Tang, Runli; Xie, Yujun; Mei, Anyi; Han, Hongwei; Li, Qianqian; Li, Zhen
<x xml:space="preserve">Abstract</x> A novel approach for enhancing the performance of dye‐sensitized solar cells is presented. It is based on the analysis of five sensitizers by utilizing triarylamine as donor, thiophene benzothiadiazole as chromophore and substituted thienyl linked with cyanoacrylic acid as the anchoring group (LI‐80‐LI‐84). Accompanied with the increasing steric hindrance of the substituents on the thienyl isolation group, the conformation of the dyes, in particular the angle between the chromophore and the anchoring group, becomes more and more twisted. Surprisingly, sensitizers with poorer conjugation effects (the higher twisted conformation) achieve better photovoltaic performances, showing a contrary trend to the traditional donor‐(π‐spacer)‐acceptor dyes with a better co‐planarity. On the basis of the preceding fundamental comprehensions, an empirical method is successfully applied to a new phenyl‐based system (LI‐85 and LI‐86) to improve their performances. The systematical investigation indicates that the twisted structures can contribute to the ECB of the TiO2 film, electron lifetime and resistance at the TiO2/dye/electrolyte interface. Thereby, the efficiency of the initial LI‐80‐based cell has been dramatically improved to 2.45 times higher for LI‐86‐based cell, paving a new way for the design of better sensitizers with higher device performances.